Types of Figurative Language in Miley Cyrus’s Songs: Hyperbole and Metaphor - Ni Nyoman Ayu Krisnawati; Ida Bagus Gde Nova Winarta; Ni Nyoman Deni Ariyaningsih (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2021)
In semantics, there are five important parts and one of those parts is figurative language. Figurative language is the use of words that makes the readers have to make a good interpretation not only by seeing what the words refer to or what it is said on the text, but also by interpreting it from the context. According to Anderson (2005:4), Figurative language is language used in an imaginative way; different from the usual or basic meaning. The aim of this study is to find out the types of figurative language in the song lyrics of Miley Cyrus’s “Breakout” album. The data were collected by listening to the song repeatedly so that they can understand the meaning of the song especially on the figurative language, searching the lyric on the internet or watching lyric video from YouTube, reading the lyrics while listen to the song, classifying the words, phrases, and sentences of the song lyric that contain of figurative language. Furthermore, in this study the writer used qualitative descriptive method. The data were also analysed by tabulating the data. The result of this study is presented in the form of sentences. The writer analysed the songs by reading them intensively. Afterwards, the writer examined the types of figurative language of the song lyrics. After analyzing the sentence in the song lyrics, the writer found two types of figurative languages that are used in the song lyrics; they are hyperbole and metaphor. The most dominant of figurative language used is hyperbole.